THE EFFECT OF SENSORY MARKETING ON THE REPURCHASE INTEREST OF KFC JEMBER CONSUMERS WITH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE - Prabatwati, Titis Alvita; Sari, Maheni Ika; Wibowo, Yohanes Gunawan (Univesitas Muhammadiyah Tangerang, 2025)
This research endeavors to analyze the impact of sensory marketing on the repurchase intentions of KFC patrons in Jember City, considering consumer satisfaction as a mediating variable. The study is grounded in the competitively expanding fast-food industry in Indonesia, where KFC holds a prominent position. Sensory marketing strategies, encompassing the stimulation of senses through aromas, interior aesthetics, ambient music, and food textures, are posited to elevate consumer experience and engender loyalty. Employing a quantitative approach, the study utilizes Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Data were gathered via questionnaires administered to 150 respondents, selected through purposive sampling, who had previously patronized KFC Jember. Analytical results indicate that sensory marketing exerts a positive and significant influence on both repurchase intention (β=0.548; p<0.05) and consumer satisfaction (β=0.321; p<0.05). Furthermore, consumer satisfaction demonstrably impacts repurchase intention positively (β=0.296; p<0.05). Consumer satisfaction also functions as a significant partial mediator in the relationship between sensory marketing and repurchase intention (β=0.095; p<0.05). These findings underscore that sensory marketing elements, such as the distinctive aroma of the food and the inviting ambiance of the restaurant, augment consumer satisfaction, thereby cultivating a positive impression and fostering repurchase inclinations. Practically, this research advocates that KFC Jember should fortify sensory elements, diversify its menu offerings, and provide enhanced customer service training to its staff.